TEACHER TALK IN TEACHING WRITING INTERACTION OF TECHNICAL ENGINEEERING STUDENTS IN SMK SWASTA TELADAN MEDAN - Sutar Oktaviana Tampubolon (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This present, study focuses on the teacher talk in teaching writing which conducted in a eleventh grade classroom of SMK Swasta Teladan Medan and to describe how the categories teacher talk affect the students’ learning process during the teaching writing to the eleventh grade of SMK Swasta Teladan Medan. In this research, the FLINT is used to identify the categories of teacher talk occur during the learning process. Moreover, this study is conducted on the form of descriptive qualitative research where the researcher as the non-participant observer on the classroom. The subject of this study is a vocational high school English teacher and the eleventh graders of SMK Swasta Teladan Medan. From the data that has been taken, it is obtained that the categories of teacher talk used by the teacher in teaching writing interaction in the eleventh grader of SMK Swasta Teladan Medan are deals with feeling, praises or encourages, jokes, uses ideas of students, repeats students response verbatim, asks question, gives information, corrects without rejection, gives direction, and criticizes student behavior. More over the categories of teacher talk used also have been proven to help the students understand better about the subject and elicit students’ contribution during the learning process. In conclusion, the researcher has found that the teacher who teaches writing in an eleventh grade classroom of SMK Swasta Teladan Medan has performed some categories of the teacher talk from FLINT.